Robots and Drones on Battlefields: New Capabilities and Emerging Challenges - Trzun, Zvonko (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
Recent armed conflicts have proved the undeniable value of systems commonly called robots or drones. The astonishing success of Azerbaijan in the 2020 Nagorno-Karabakh conflict, largely attributed to the strategic use of unmanned aerial vehicles (UAVs) by the Azerbaijani military, left experts and analysts in awe. However, the worth of UAVs had already been proven years earlier with the advent of the multi-role MQ-1 Predator.This chapter provides a concise overview of UAV development, current capabilities, and potential future directions. The text is structured so that the first part describes the development of UAVs, and the second part focuses on unmanned ground vehicles (UGVs). The third part examines the extent to which Europe has embraced these new armed systems, analysing both European armed forces and industries – both striving to catch up with the main players in the unmanned vehicles market.The chapter also describes the general shift in the world’s security landscape, the rising sense of uncertainty, the long-forgotten fear of war, and the consequential surge in spending on military equipment. The development of artificial intelligence (AI) and the increasing autonomy of drones are briefly touched upon as this is an emerging field with the first AI-controlled systems still being tested. However, it is a topic deserving of a completely separate discussion. These points ultimately underscore the technical issues accompanying the usage of UAVs and UGVs, which occasionally lead to tragic errors. Whether the likelihood of such errors will decrease or increase as AI eventually replaces humans in controlling drones (“human out-of-the-loop”) is likely to become evident in the very near future.Keywords: drones, robots, unmanned aerial vehicles, unmanned ground vehicles, European military industry, artificial intelligence